Indocyanine-guided ureter resection for radical cystectomy: a systematic review and meta-analysis - Haney, Caelán Max; Studier-Fischer, Alexander; Geißler, Mark Enrik; Ohlmeier, Jakob; Westhoff, Niklas Christian; Stolzenburg, Jens-Uwe; Michel, Maurice Stephan; Kowalewski, Karl-Friedrich (BJU international, 2025)
Objectives To perform a systematic review and meta-analysis of studies comparing indocyanine green (ICG)-guided resection of ureters with the standard of care during radical cystectomy (RC). Methods The Cochrane Central Register of Controlled Trials (CENTRAL), Medical Literature Analysis and Retrieval System Online (MEDLINE) and Web of Science were searched for studies comparing ICG-guided resection of ureters with the standard of care during RC. The primary outcome was the rate of uretero-intestinal stenosis (UIS) per patient, secondary outcomes included the rate of UIS per ureter, major and minor complications; re-interventions due to UIS, re-admissions and the length of ureter resected. Data were pooled as odds ratio (OR) or mean difference with a random-effects model. Risk of bias was assessed using the Risk Of Bias In Non-randomised Studies of Interventions (ROBINS-I) tool and the Grading of Recommendations, Assessment, Development, and Evaluation (GRADE) approach was used to assess certainty of evidence. The systematic review was registered prospectively via the International Prospective Register of Systematic Reviews (PROSPERO: CRD42024545516). Results In all, 11 studies totalling 1339 patients were identified. ICG-guided resection led to a statistically significant decrease in UIS per patient (OR 0.20, 95% confidence interval [CI] 0.07-0.52) and per ureter (OR 0.17, 95% CI 0.06-0.50). There were statistically significantly fewer major complications, re-interventions due to UIS in the ICG-guided group, there was no difference in minor complications and re-admissions. Certainty of evidence was low. Conclusions With low certainty of evidence, ICG-guided resection of ureters lowers the rate of UIS. A standardisation of grading of UIS is needed. The time for randomised controlled trials in this setting is now.